A case study on the use of Public Narrative as a leadership development approach for Patient Leaders in the English National Health Service - Aiello, Emilia; Perera, Kathryn; Ade, Mo; Sordé-Martí, Teresa (Frontiers in Public Health, 2022)
Background. In 2016 the National Health Service (NHS) England embraced the commitment to work for maternity services to become safer, more personalized, kinder, professional and more family-friendly. Achieving this involves including a service users’ organizations to co-lead and deliver the services. This article explores how Public Narrative, a framework for leadership development used across geographical and cultural settings worldwide, can enhance the confidence, capability and skills of service-user representatives (or Patient Leaders) in the NHS in England. Specifically, we analyse a pilot initiative conducted with one cohort of Patient Leaders, the Chairs of local Maternity Voices Partnerships (MVPs), and how they have used Public Narrative to enhance their effectiveness in leading transformation in maternity services as part of the NHS Maternity Transformation Programme. Methods. Qualitative two-phase case study of a pilot training and coaching initiative using Public Narrative with a cohort of MVP Chairs. Phase 1 consisted of a 6-month period, during which the standard framework was adapted in co-design with the MVP Chairs. A core MVP Chair Co-Design Group underwent initial training and follow-up coaching in Public Narrative. Phase 2 consisted of qualitative data collection and analysis. Results. The study of this pilot initiative suggests two main ways in which Public Narrative can enhance the effectiveness of Patient Leaders in service improvement in general and maternity services in specific. First, training and coaching in Public Narrative enables Patient Leaders to gain insight into, articulate and then craft their lived experience of healthcare services in a way that connects with and activates the underlying values of others (“shared purpose”), such that those experiences become an emotional resource on which Patient Leaders can draw to influence future service design and decision-making processes. Second, Public Narrative provides a simple and compelling structure through which Patient Leaders can enhance their skills, confidence and capability as “healthcare leaders”, both individually and collectively. Conclusions. Public Narrative can significantly enhance the confidence, capability and skills of Patient Leaders, both to identify and coalesce around shared purpose and to advance genuine co-production in the design and improvement of healthcare services in general and maternity services in specific.